HUBUNGAN DISIPLIN KERJA DAN LINGKUNGAN KERJA DENGAN KINERJA PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT UMUM DAERAH TUGUREJO SEMARANG - Alessandra Lourdess Sutrisnoputri; Chriswardani Suryawati; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2018)
Nurses are very important human resources in a hospital. Therefore, the contribution of inpatient nurses greatly determines the performance of the hospital. There are many factors that affect the performance of inpatient nurses in improving the quality of services, such as salary, work environment, work discipline, leadership style, job satisfaction, motivation, and organizational culture. The nursing care quality of a hospital is assessed with BOR, LOS, TOI data. These data indicate a decrease in the performance of inpatient nurses in Semarang’s Tugurejo General Hospital. Work discipline and work environment are the factors causing the low performance quality of inpatient nurses at Tugurejo Hospital. In that case, this study aims to find the correlation of work discipline and work environment with the performance of nurses in the inpatient room of Tugurejo Hospital. The type of this research is quantitative research with cross sectional approach. The samples used in this research are 80 respondents. The results showed that 47% of the respondents are 26-35 years old, 58% of the respondents are female, 62% of the respondents have worked for ≤10 years, and 42% of the respondents are bachelors of nursing major. The result of the research shows that the variables related to the performance of inpatient nurses are work discipline with low relation strength (p value = 0,000), while work environment is unrelated (p value = 0,332). Hospitals are suggested to standardize their operational procedures of technical aspects of nurse work. Hospitals are also suggested to provide hand-washers and antiseptic soaps that are easily accessible so that inpatient nurses can wash their hands first before starting work. Meanwhile, nurses are demanded to obey the rules and utilize their work time well.